ANALISIS LAGU BUNDA CIPTAAN MELLY GOESLAW - Levi Zahardi; Jagar Lumban Toruan; Erfan Lubis (FBS Universitas Negeri Padang, 2017)
This research is intended to analyze “Bunda” song written by Melly Goeslaw in terms of song structure and melody composition. This research is categorized into qualitative study conducted by applying content analysis approach. The theories used to analize the data were those related to melody structures, melody composition, and song forms. The data were obtained through documentation study, library study, and lab work. The results of the research reveal that “Bunda” song has combination of strong and faint taps and uses stepping and jumping style. It has 90 tempo with 4/4 cadence. The musical cord used is major and the dominant interval is seconded. This song has 12 ranges of musical notes. The formulation of the melody is the combination of rising, flattening, and lessening melodies. The progressing accords applied were not only the basic accords but also the connecting ones that could bridge the move from the basic accord. This movement makes the song flow and sway smoothly. “Bunda” song has 2 basic motives, 15 developed motives, 4 antecedent phrases, and 5 consequent phrases. The song has two forms; A and B. The melody and the lyrics are dominantly in the form of syllabic. This song is classified into Logogenic (text- focused). The song comprises of several major accords, namely tonica, supertonica, subdominant, sub-median, and connecting accords (median and dominant). “Bunda” song has two cadences including the Perfect Authentic Cadence and The Authentic Half Cadence. Although the song has melismatic and neumatic forms, it is dominated by syllabic form. Key word: Analysis, Song Structures, “Bunda” Song.